2021
DOI: 10.1371/journal.pone.0245878
|View full text |Cite
|
Sign up to set email alerts
|

Daikenchuto increases blood flow in the superior mesenteric artery in humans: A comparison study between four-dimensional phase-contrast vastly undersampled isotropic projection reconstruction magnetic resonance imaging and Doppler ultrasound

Abstract: Respiratory-gated four-dimensional phase-contrast vastly undersampled isotropic projection reconstruction (4D PC-VIPR) is magnetic resonance (MR) imaging technique that enables analysis of vascular morphology and hemodynamics in a single examination using cardiac phase resolved 3D phase-contrast magnetic resonance imaging. The present study aimed to assess the usefulness of 4D PC-VIPR for the superior mesenteric artery (SMA) flowmetry before and after flow increase was induced by the herbal medicine Daikenchut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…28 Another advantage of MRI is the ability to perform additional analysis using the captured data. 31…”
Section: Discussionmentioning
confidence: 99%
“…28 Another advantage of MRI is the ability to perform additional analysis using the captured data. 31…”
Section: Discussionmentioning
confidence: 99%
“…However, the duration of fasting in previous reports has not been consistent, ranging from 2 to 6 h [ 8 , 11 , 12 , 14 , 16 , 23 26 ]. In addition to dietary effects, some herbal medicines increase intestinal blood flow [ 47 ].…”
Section: Technical Considerations Of 4d Flow Mri In the Portal Systemmentioning
confidence: 99%
“…The anti-in ammatory effect of DKT are attributed to the fact that DKT manages the downregulation of cyclooxygenase 2 (COX-2), the upregulation of endogenous adrenomedullin (ADM), and the suppression of eosinophil in ltration 15 . The regulation of intestinal blood ow by DKT is achieved by stimulating epithelial transient receptor potential ankyrin 1 (TRPA1) to induce endogenous ADM release 16,17 . Recent studies have suggested that DKT can alter the gut microbiota, thereby improving long-lasting dysbiosis and gastrointestinal dysfunction after bowel or liver surgery 18,19 .…”
Section: Introductionmentioning
confidence: 99%